Social interest housing projects implemented by BNH in the 1980s in Campo Grande, Mato Grosso do Sul - Hokama, Kelly Cristina; Oliveira, Ademir Kleber Morbeck; Matias, Rosemary (National Journal of City Management, 2022)
The conditions that existed in 1964 allowed the foundation of the Housing Finance System and the National Housing Bank (BNH), which led to the creation of large social housing projects the Housing Companies (COHABs). These projects were implemented to reduce the pressure for housing on the classes with lower purchasing power. This article aims to evaluate housing projects of social interest implemented in the 1980s through the BNH in Campo Grande, Mato Grosso do Sul, analysing their implementation and consequences. The document analysis method was used on data characterising the occupied areas. The BNH action was significant due to the number of housing units delivered in the period, which benefitted 13,028 families, 58,626 people. The model followed considerably reduced the housing deficit, but also led to the formation of urban voids; this was related to the fact that the BNH is a central decision-making body at the federal level. Housing construction used areas in regions that were unattractive for the formal real estate market, in places far from the centre, which were often located on the banks of streams, outside the urban perimeter. This situation made it difficult for the population to access service, mobility, supply, and urban facility networks. At the end of the period evaluated, the need to improve public policies aimed at social housing became evident, in future avoiding some mistakes made in the implementation of housing projects in the city.